Organizing pneumonia as the first manifestation of anti-synthetase syndrome. (December 2016) - Priyangika, S.; karunarathna, W.; Liyanage, Isurujith; Gunawardana, Methsala; Udumalgala, Sumeda; Rosa, Chamith; Kulatunga, Aruna
Abstract Background Anti-synthetase syndrome associated interstitial lung disease can occur either simultaneously, before, or after the development of polymyositis/dermatomyositis. Histology of interstitial lung disease can be nonspecific interstitial pneumonia, usual interstitial pneumonia, diffuse alveolar damage, organizing pneumonia. Organizing pneumonia associated anti-synthetase syndrome is a rare finding especially as the first manifestation. Case presentation We report a 41 year old male patient who presented with organizing pneumonia and 2 years following the onset, developed polymyositis with anti-JO-1 antibody positivity. Conclusion It is important to screen patients with organizing pneumonia for anti-synthetase syndrome which can be manifested later.